2021
DOI: 10.3390/en14206776
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency in the Industry 4.0 Era: Attributes of Teal Organisations

Abstract: The rapid development of innovations in the industry 4.0 era led to new or evolved companies. At the same time, the accepted concept of carbon-free development requires building a new philosophy for the company’s management. The paper aims to analyse the key attributes of teal organisations (as a new type of a company) from the energy sector (as a core sector for carbon-free transformation). The paper summarises the core features of teal organisations and their attributes. In the paper, three hypotheses are te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 58 publications
0
26
0
2
Order By: Relevance
“…In [43] it was found that, for 16 EU countries from 1990-2017, ICT and power use increase caused CO 2 emissions to grow and GDP to rise. Miśkiewicz et al [44] analyzed climate change, innovation and information technology, and CO 2 emissions for Visegrád countries (Hungary, Poland, Check Republic, and Slovakia) from 2007-2016 and found the development of information and innovation technologies had a statistically significant effect on CO 2 emissions. Furthermore, according to [40], despite the consumption of ICT goods and services being argued to directly aggravate the CO 2 emissions into the atmosphere, the impacts can indirectly be reversed through the ICT-enabled enhancement of energy use efficiencies and greening of the ICT sector.…”
Section: The Literature Reviewmentioning
confidence: 99%
“…In [43] it was found that, for 16 EU countries from 1990-2017, ICT and power use increase caused CO 2 emissions to grow and GDP to rise. Miśkiewicz et al [44] analyzed climate change, innovation and information technology, and CO 2 emissions for Visegrád countries (Hungary, Poland, Check Republic, and Slovakia) from 2007-2016 and found the development of information and innovation technologies had a statistically significant effect on CO 2 emissions. Furthermore, according to [40], despite the consumption of ICT goods and services being argued to directly aggravate the CO 2 emissions into the atmosphere, the impacts can indirectly be reversed through the ICT-enabled enhancement of energy use efficiencies and greening of the ICT sector.…”
Section: The Literature Reviewmentioning
confidence: 99%
“…Digital transformation and business strategy development allow organizations to adapt to their client's individual needs [29,30], to follow the trends in the business sector [31,32], and to align with each other in the value networks [33,34]. These changes enable organizations to gain a competitive advantage [35,36] and possibly sustainability [37,38] based on digitalization [9,39] and technology implementation [40,41] called digitization [42]. Digitization involves the use of (Information and Communication Technologies) ICT solutions to increase the efficiency of the existing processes [43,44] through automation [45,46].…”
Section: Literature Review 21 Definitional Issuesmentioning
confidence: 99%
“…Companies presented above as the examples of the most important business models [111,116] are the source of inspiration [19] for the energy sector companies [40] involved in energy generation, transfer, distribution, and sell [23,68]. We intentionally do not mention the energy sector companies to avoid bias [117,118].…”
mentioning
confidence: 99%
“…This article uses a broad interpretation of the AI era, which is not limited to AI alone and covers the whole set of disruptive (subversive) technological innovations of Industry 4.0, in particular, robots, Big Data and data analytics, as well as the Internet of Things (IoT). All technologies of the AI era are characterized by high energy intensity, which was the criterion for their generalization in the works of Hao et al (2022), Miśkiewicz et al (2021), Reshetnikova and Pugacheva (2022), Wang et al (2022).…”
Section: Introductionmentioning
confidence: 99%